SIDIK JARI DNA PLASMA NUTFAH PADI LOKAL MENGGUNAKAN MARKA MOLEKULER SPESIFIK UNTUK SIFAT PADI BERAS MERAH - Dwinita W Utami; Aderahma Ilhami; Ida Hanarida (BERITA BIOLOGI, 2010)
Red rice is one corp that has genetic variation both based upon phenotype and genotype evaluation using moleculer markers for specific gene. A research objective is to identify genetic diversity using red rice specific molecular markers. Forty accessions of Indonesian local rice included 9 accessions of red rice germplasm were used as genetic materials for this research. Specific molecular markers (RC3, RC9 and RC12) for a pigment color found in rice seed were designed based on alignment sequence analysis to rc-bHLH gene, a transcription factor for prothocyanidine protein. Then these markers were used to analyze the genetic variation of red rice. Cluster analysis and association test between phenotype and genotype performances were analyzed by TASSEL 2.1 software program. Results showed that red rice accessions distributed into 2 cluster. One cluster is more closely related to white rice than the other. The association test showed RC12 is the most significant marker in association with the red rice trait: red pericarp and white aleuron. These phenotype variations were found in Cempo merah, one accession originated from Yogyakarta and Pulut mandoti, one accession from South of Sulawesi.